Ethnobotanical study of endemic and non-endemic medicinal plants used by indigenous people in environs of Gullele botanical garden Addis Ababa, central Ethiopia: A major focus on Asteraceae family - Woldeamanuel, Melaku Masresha; Geda, Mohammed Kasso; Mohapatra, Shibani; Bastia, Tapan Kumar; Rath, Prasanta; Panda, Alok Kumar (Frontiers in Pharmacology, 2022)
Gullele Botanical Garden (GBG) in Addis Ababa, Ethiopia is a joint venture of Addis Ababa government and the university. The garden has been built mainly to conserve the endemic plants and to advance the research on the endemic and non-endemic plants collected from different part of Ethiopia. Many traditional healers from the environs of GBG and different subcities of Addis Ababa depend on the garden for their practice of traditional medicine but there is no systematic documentation of the traditional medicinal knowledge of these healers. The main objective of the present study is to comprehensively document the ethnobotanical and ethnomedicinal information from the traditional healers of different ethnic and cultural groups depending on GBG and to create a database of the endemic plants used by these healers. The ethnobotanical and ethnomedicinal data obtained from 60 traditional healers have been analyzed both qualitatively and quantitatively. A total of 81 medicinal plants belonging to 47 families have been identified. Majority of the plants used belonged to Asteraceae (12) family. The most frequently used plant form and plant parts are herbs and leaves. The major method adopted by the healers for preparation and administration of traditional medicine is crushing and topical, respectively. Skin and general diseases are the most important ailments treated by the healers. The three most cited plants used to treat diseases are Echinops kebericho Mesfin (60), Hagenia abyssinica (Bruce) J.F.Gmel (60) and Laggera tomentosa (A.Rich.) Sch.Bip. ex Oliv. & Hiern (58). The present study is the first systematic, qualitative, and quantitative ethnobotanical analysis and documentation done on the use of the medicinal plants from GBG for traditional medicine. In addition, our study reveals that E. kebericho is endemic and endangered plant and is highly used in traditional medicine. Therefore, GBG authorities should take steps for the propagation and restoration of this plant. Further it is suggested that the pharmacological properties of the roots and leaves of E. kebericho should be compared to find the possibility of use of leaves in place of roots for the preparation of traditional medicine which would help in conserving this endemic plant of Ethiopia.